Inflation targeting: analyzing indicators of inflation in Finland - Kaare G. Andersen (Bank of Finland, 1995)
This paper considers different indicators of inflation that are recorded in Finland.Initially, we define inflation as an irreversible rise in the general price level.We then go on to describe different indicators of inflation, focusing on problems related to their construction.Since it is not possible to monitor the general price level, we have to target a subset of this.The different indicators each measure representative parts of the economy.However, we found that they all have strengths and weaknesses and the choice of an indicator is thus a balance between different priorities.We then conducted an empirical analysis of these indicators of inflation with respect to stationarity and cointegration using data for Finland.Empirical evidence supports the assumption of cointegration between different indicators of inflation, but we also found that price levels are non-stationary. Finally, this paper discusses special issues that should be borne in mind when choosing an inflation indicator as a target objective for monetary policy.
URN:NBN:fi:bof-20140807378
Keywords: 330